2018
DOI: 10.1016/j.exger.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal cells: Roles in atrophy and age-associated dysfunction of the thymus

Abstract: Atrophy of the thymus, the primary site of T lymphocyte generation, is a hallmark of the aging immune system. Age-associated thymic atrophy results in diminished output of new, naïve T cells, with immune sequelae that include diminished responses to novel pathogenic challenge and vaccines, as well as diminished tumor surveillance. Although a variety of stimuli are known to regulate transient thymic atrophy, mechanisms governing progressive age-associated atrophy have been difficult to resolve. This has been du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 106 publications
1
40
0
Order By: Relevance
“…Of particular interest is the observation that the thymus is remarkably sensitive to inflammation (e.g., sepsis or experimental LPS-induced thymic involution) and oxidative stress which leads to thymic involution that seems to be irreversible [79][80][81][82][83][84]. Deleterious pro-apoptotic effects on both thymus stromal cells and intrathymic T cells are underlying this phenomenon.…”
Section: Oxidative Stress Inflammation and Premature Immunological Amentioning
confidence: 99%
“…Of particular interest is the observation that the thymus is remarkably sensitive to inflammation (e.g., sepsis or experimental LPS-induced thymic involution) and oxidative stress which leads to thymic involution that seems to be irreversible [79][80][81][82][83][84]. Deleterious pro-apoptotic effects on both thymus stromal cells and intrathymic T cells are underlying this phenomenon.…”
Section: Oxidative Stress Inflammation and Premature Immunological Amentioning
confidence: 99%
“…On the contrary, the thymus, which reaches its maximal size and T cell output during early postnatal life, exhibits early thymic involution, a phenomenon that becomes even more prominent with advancing age [12,13,[18][19][20][21]. Although the size of the human thymus seems to remain unchanged throughout life under normal conditions [22], in other vertebrates, it declines during aging [23]. Nevertheless, in almost all vertebrates having a thymus, thymic cellularity is progressively decreased and replaced by adipose tissue over time, resulting in perturbation of the normal tissue architecture [14,21,24,25] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Even though age-associated thymic regression represents one of the most recognizable features of the aging immune system, the underlying mechanisms are not well understood [33]. Several candidates have been proposed, suggesting that thymic regression involves the interplay of various and different mechanisms ( Figure 2); interestingly, there are lines of evidence that in this complex process, the thymic stroma and especially the TECS are the most sensitive compartment [12,23,27,34]. A number of studies reported that sex steroid hormones, and especially androgens, contribute to ageassociated thymic involution [12,23,27,35] (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thymus, as a central immune organ, is the main site for generation of naive T lymphocytes [43]. Thymus atrophy is considered to be a biomarker of immune system aging and is influenced by many factors, such as age, hormones, and gender [44].…”
Section: Discussionmentioning
confidence: 99%